The Death Ritual in Bataknese Culture - Simangunsong, Nora Ervina; herlyna, Herlyna; Priyoto, Priyoto (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
In Batak society there are various kinds of rituals that have long been passed down from their ancestors and these rituals are still very much adhered to today. Starting from birth, marriage, death, to the stages of entering a new house, everyone uses ritual. However, this research focuses on Death Ritual in the Bataknese Culture especially in Batak Toba. The Death Ceremonies are also different. Starting from newborn children, toddlers, teenagers, for those who are married, already have children and even for those who are already having grandchildren also has different rituals. This research aims to introduce Batak culture, especially the tradition of death, which has a variety of differences, and at the same time invite young Batak people to preserve Batak customs so that they do not become extinct over time. Death ritual often involve various complex rites and traditions, such as traditional ceremonies, funeral processions, traditional ceremonies, and a series of activities aimed at sending the spirit of the deceased to another world peacefully. Apart from that, there is also a belief that the relationship between living people and the spirits of the deceased remains, and this ceremony is also a way to maintain this relationship